Multifactorial determinants of NK cell repertoire organization: insights into age, sex, KIR genotype, HLA typing, and CMV influence - Enora Ferron; Enora Ferron; Enora Ferron; Gaëlle David; Gaëlle David; Gaëlle David; Catherine Willem; Catherine Willem; Catherine Willem; Nolwenn Legrand; Nolwenn Legrand; Nolwenn Legrand; et al. (Frontiers in Immunology, 2024)
IntroductionPolymorphisms in the KIR and HLA genes contribute to the diversity of the NK cell repertoire. Extrinsic factors also play a role in modifying this repertoire. The best example is cytomegalovirus, which promotes the expansion of memory-like NK cells. However, the mechanisms governing this phenotypic structure are poorly understood. Furthermore, the influence of age and sex has been understudied.MethodsIn this study, we examined these parameters in a cohort of 200 healthy volunteer blood donors, focusing on the major inhibitory KIR receptors and CD94/NKG2A, as well as the differentiation marker CD57 and the memory-like population marker NKG2C. Flow cytometry and two joint analyses, unsupervised and semi-supervised, helped define the impact of various intrinsic and extrinsic markers on the phenotypic structure of the NK cell repertoire. ResultsIn the KIR NK cell compartment, the KIR3DL1 gene is crucial, as unexpressed alleles lead to a repertoire dominated by KIR2D interacting only with HLA-C ligands, whereas an expressed KIR3DL1 gene allows for a greater diversity of NK cell subpopulations interacting with all HLA class I ligands. KIR2DL2 subsequently favors the KIR2D NK cell repertoire specific to C1/C2 ligands, whereas its absence promotes the expression of KIR2DL1 specific to the C2 ligand. The C2C2Bw4+ environment, marked by strong -21T motifs, favors the expansion of the NK cell population expressing only CD57, whereas the absence of HLA-A3/A11 ligands favors the population expressing only NKG2A, a population highly represented within the repertoire. The AA KIR genotype favors NK cell populations without KIR and NKG2A receptors, whereas the KIR B+ genotypes favor populations expressing KIR and NKG2A. Interestingly, we showed that women have a repertoire enriched in CD57- NK cell populations, while men have more CD57+ NK cell subpopulations. DiscussionOverall, our data demonstrate that the phenotypic structure of the NK cell repertoire follows well-defined genetic rules and that immunological history, sex, and age contribute to shaping this NK cell diversity. These elements can contribute to the better selection of hematopoietic stem cell donors and the definition of allogeneic NK cells for cell engineering in NK cell-based immunotherapy approaches.cters are displayed correctly.